CMV-associated adrenal insufficiency in a renal transplant recipient. (2018) - Tejura, Nilesh; Sonyey, Alexandra
Abstract: Adrenal insufficiency is a rare manifestation of tissue-invasive cytomegalovirus (CMV) disease. CMV is one of the leading opportunistic pathogens affecting renal transplant recipients. Its prevalence in the adrenal glands of autopsied AIDS cases has been well documented. We report a rare case of CMV-associated adrenal insufficiency in a renal transplant recipient.